Searching for the Standard: The Impact of Level of Training on In Vivo Coaching in Parent-Child Interaction Therapy. Issue 1 (January 2023) - Niec, Larissa N.; Brodd, Irene; Schoonover, Ciera E.
Although live coaching using behavioral principles is a powerful mechanism of change in behavioral parent training (BPT), little research has examined the coaching process. We used a cross-sectional sample of coaches with different levels of training in the evidence-based behavioral parent training model parent-child interaction therapy (PCIT) to begin to understand how training impacts coaching techniques. Forty-six coaches including PCIT lay helpers, therapists, within-agency and global/regional trainers, provided a sample of coaching in response to a standardized parent-child interaction. Level of training was significantly and positively associated with coaching verbalizations ( r (44) = .80, p  < .001). Training level was also associated with effective coaching strategies such that as training increased, coaches used more strategies related to positive treatment outcomes for families. Results suggest that coaches with less training may benefit from additional education around certain types of responsive coaching strategies. Findings raise important questions about how "adequate" and "optimal" coaching might be defined.